PERANCANGAN BRANDING LAXMI CAKE AND BAKERY SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Rosyidah, Khurriyatur; Bahruddin, Muh; Sutrisna, Andika Agung (Jurnal Art Nouveau, 2015)
Abstract: LAXMI cake and bakery is a growing culinary company and has several branches in Gresik, Tuban, and Lamongan. The problem is, a lot of competitors threaten the sales position of LAXMI cake and bakery. During this, media campaign that used by LAXMI cake and bakery does not have concept design. The low awareness of the importance the media campaign, create a high probability of customers moving to another bakery. Media campaigns are very important to build brand equity. Therefore, it is necessary to increase customer loyalty by doing branding and maintenance customers through the media campaign to maintain the position of LAXMI cake and bakery from the competitors. The design is done by observation, interviews, depth interviews, and literature studies using qualitative-descriptive analysis and supported by existing analysis, SWOT and STP obtained unique and luxury concept that is used in overall design. The concept of unique and luxury implemented using product photo illustration of LAXMI cake and bakery. Unique concept realized by unique form of media, while the luxury concept realized from the arrangement of layout and color selection. The concept was subsequently applied in corporate identity and promotional media that can be able to increase customer loyalty.Â Keywords: Design, Branding, LAXMI cake and bakery, Brand Loyalty, Unique and Luxury.